The implementation of an effective compliance program as exemption or mitigating factor of liability of administrative infrigements - Zúñiga Diaz, Giuliana (2020)
This paper addresses the study of compliance programs and initially explores their treatment as exemptions and mitigations factors of responsibility in criminal matters, and then analyzes the possibilities and manifestations of said institution as part of the Peruvian sanctioning administrative system. Our proposal is based on taking into account the subjection of the sanctioning administrative system to the so-called ius puniendi, and in this sense, we are inclined to include –and adapt based on the nuances of the sanctioning administrative law– of effective compliance programs as an exemption or mitigation of administrative responsibility.